Book review of Wahhabism and the rise of New Salafist: theology, power & Sunni Islam - Mohamad Nasir, Mohamad Nasrin (The Islamic Foundation, 2023)
A book review published by Muslim World Book Review (UK). The book, Wahhabism and the Rise of New Salafist. Theology, Power & Sunni Islam was written by Namira Nahouza. The book was published by I.B.Tauris, UK.